Estratégias conversacionais: marcas de interação linguística na obra de João Antônio Malagueta, Perus e Bacanaço - Carmo, Teresinha de Oliveira (2014)
This research has as its purpose to emphasize the conversational strategies that the characters utilize to interact in communicative situations. The purpose of the current work is for it to be applied to the teaching of the Portuguese Language. Aiming thus for the awareness that working oral language goes beyond reading out loud. Also have the student understand the importance of studying the marks of orality present in texts. Contribute to form a conscience society, less prejudice and knowledgeable of the linguistics variations and know how to adapt them to its convivial. Therefore, we utilized the tale Malagueta, Perus, and Bacanaço by João Antônio as corpus. In the tale, the author describes the trickery of the center of São Paulo tracing a parallel between what is real the fight for survival by a marginalized class in the end of the 50th decade and the fiction, a vivid adventure lived by Malagueta, Perus, and Bacanaço, who are passionate about the game of pool. We searched in the work the marks of oralities and expressions that were used by the author as strategies, mainly, of interaction. Beyond identifying which mechanisms of comicality in the present narrative contributed to a greater clarity and enrichment of the work. The author utilizes humoristic mechanism that contribute on taking the reader to have fun, reflect, and be offended with the events, sometimes, apparently banal, but with marks of violence implicit in the text. So theoretically we base research in interactional sociolinguistics with prof. Dino Preti, in conversation analysis, with Marcuschi and discourse analysis, with Eni Orlandi. Since this research, one can notice that the conversational strategies, contribute to provide us with expressive examples of language in the São Paulo sub world